Global education: promoting reader's digest in extensive reading for understanding diverse cultures / Tuan Sarifah Aini Syed Ahmad ... [et al.]. - Syed Ahmad, Tuan Sarifah Aini; Tengku Mahmood, Tengku Farah Petri; Hasan, Nor Haniza; Soo, Kum Yoke (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Developing global competencies through global education is imperative in today’s world. It prepares students to understand, function and develop in global communities. One of the competencies that is essential in today’s interconnected world is understanding various cultures all around the world. It may help them to increase their cultural awareness, which is crucial in making them see and respect other perspectives. Moreover, cultural awareness may also facilitate them in appreciating the essential values of people from various places. It may also prove beneficial in the future when students engage in professional environments that require collaboration with individuals from diverse cultures. Students must immerse themselves in communities that actively practice different cultures to fully understand them and prepare for future endeavours. A common way to have immersion is by travelling to the places and staying in the communities for a period of time. However, not many people can afford to do this as they may have constraints such as financial support, time limitations and language barriers. Therefore, they need to opt for a more affordable way to learn about different cultures.